FEMINIST AND STRUCTURAL NARRATOLOGIE AS IDENTITY (RE)-CONFIGURATIONS IN AFRICAN NARRATIVES: A META-CRITICAL EXPOSITION OF LITERARY ARTICLES - Christopher Babatunde Ogunyemi (English Review: Journal of English Education, 2017)
Research in African literature articulated a number of literary and philosophical theories, particularly in the way that they can potentially undo conventional understandings of gender in the Nigerian context. This paper seeks to apply these insights in the form of a critical narratology.  Although narratology has a structuralist or formalist orientation, having its theoretical beginning in Saussure’s modern linguistics, and like structuralism, aspires to ‘scientific’ or ‘universalist’ claims, it, also, examines the way in which narratives affect the way we perceive the world. This paper will attempt to mobilise narratology critically, with the benefit of the insights emerging from various articles, in order to help our understanding of the question of gender and social themes in Nigerian post-colonial literature. Most especially, this paper will visualise the analysis of structural narratology and finally with feminist narratology in order to correct the inadequacies of structural narratology and the suppression of women in texts.Keywords: African literature, feminist narratology, gender identity, structural narratology